201. Healthcare utilization outcomes of patients prescribed fluoroquinolones on discharge from the hospital to nursing homes. (31st December 2020) - Lantz, Tyler L; Noble, Brie N; Crnich, Christopher J; McGregor, Jessina C; Chan, Dominic; Furuno, Jon P; Furuno, Jon P; Bearden, David T
Abstract: Background: Fluoroquinolones (FQs) are frequently prescribed in nursing homes (NHs) despite concerns regarding broad spectrum antibiotic selective pressure, increased risk of Clostridioides difficile infection, and other adverse events. NH antibiotics are also frequently initiated in hospitals prior to NH admission. We quantified the frequency and outcomes of patients prescribed FQs on discharge from the hospital to NHs. Methods: This was a retrospective cohort study of adult (age ≥ 18 years) inpatients prescribed a FQ on discharge from Oregon Health & Science University Hospital (OHSU) to a NH between 1/1/2016 and 12/31/2018. Study data were collected from a repository of electronic health record data. The outcome of interest was a composite of 30-day hospital readmission or emergency department (ED) visit to OHSU. Associations were quantified using odds ratios (ORs) and 95% confidence intervals (CIs). Results: Among 9, 546 patients discharged to a NH, 2, 410 (25%) were prescribed at least one antibiotic and 423 (17.6%) were prescribed a FQ. Of these patients, 36.9% were age ≤ 65, 53% were male, 11.6% received a specialty infectious diseases consultation, 34.8% had a surgical diagnosis, and 49.7% had a hospital length of stay > 7 days. The most prevalent comorbidities were cancer (30.5%), chronic obstructive pulmonary disease (29.6%), and renal disease (26%). The most prevalent FQs prescribed were ciprofloxacin (56.7%), levofloxacin (40.2%), and moxifloxacin (3.1%). Duration of NH therapy > 7 days occurred in 37.6% of patients. The most common infectious diagnoses were bloodstream infection and endocarditis (39%), pneumonia (17%), and urinary tract infection (14.2%). Of patients prescribed a FQ, 276 (65.3%) had an ED visit or hospital admission to index facility within 30 days of discharge. Patients who were ≤ 65 years old (OR 2.3, 95% CI 1.4–3.5), male (OR 1.6, 95% CI 1.1–2.5), had comorbid renal disease (OR 1.8, 95% CI 1.1–2.9), or osteomyelitis as infectious diagnosis (OR 2.4, 95% CI 1.0–5.7) were more likely to have a 30-day ED visit or hospital admission. Conclusion: Patients prescribed FQs on discharge to NHs frequently returned to the hospital for an ED visit or inpatient admission within 30 days of discharge. Disclosures: All Authors : No reported disclosures